2012
DOI: 10.5402/2012/786526
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Assessment in Patients with Multiple Sclerosis Receiving Interferon Beta-1a: A Comparative Longitudinal Study of Avonex and Its Biosimilar CinnoVex

Abstract: Background. Multiple sclerosis (MS) is an autoimmune inflammatory disease of central nervous system (CNS). MS affects quality of Life (QOL) due to physical disability and other associated problems. Disease-modifying agents like interferon beta (IFNB) have been widely utilized in this patient population; however, their frequency, route of administration, side effects, high cost, and also the question of whether they are truly beneficial for longer-term outcomes and QOL need to be further investigated. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…However, to our knowledge, there are very few studies that compared cost-effectiveness of CinnoVex with other treatment options. Two previous studies found that CinnoVex is a more cost-effective form of IFNB-1a in comparison with Avonex ( Abolfazli et al, 2012 ; Nikfar et al, 2013 ). Nikfar et al compared the cost-effectiveness of all brand INF β products for managing patients with RRMS from a societal perspective.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…However, to our knowledge, there are very few studies that compared cost-effectiveness of CinnoVex with other treatment options. Two previous studies found that CinnoVex is a more cost-effective form of IFNB-1a in comparison with Avonex ( Abolfazli et al, 2012 ; Nikfar et al, 2013 ). Nikfar et al compared the cost-effectiveness of all brand INF β products for managing patients with RRMS from a societal perspective.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies showed that it is effective in preventing relapse and reduction in disability and MRI lesions ( Etemadifar, Janghorbani, & Shaygannejad, 2006 ). CinnoVex is a new alternative produced in Iran in recent years and approved by Iranian Food and Drug Organization (IFDA) ( Abolfazli et al, 2012 ) and satisfactory results are achieved in IFDA Safety and Toxicology tests ( Sharafaddinzadeh, Majdinasab, Ghiasian, & Moravej-Aleali, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Various studies have shown its efficacy in RRMS patients in Iran. 5,6 The frequency of thrombocytopenia ranges from 0.1% to 8% in patients receiving b-interferon-1α (http://www.cinnagen.com/ Product.aspx?t=2&l=1&Id=45&f=2#ti tle32). Thrombocytopenia has also been reported in patients receiving Cinnovex in Iran (Product Information.…”
mentioning
confidence: 99%